2016
DOI: 10.4103/0974-7753.188966
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ovine dermal papilla cell aggregation

Abstract: Context:The dermal papilla (DP) is a condensation of mesenchymal cells at the proximal end of the hair follicle, which determines hair shaft size and regulates matrix cell proliferation and differentiation. DP cells have the ability to regenerate new hair follicles. These cells tend to aggregate both in vitro and in vivo. This tendency is associated with the ability of papilla cells to induce hair growth. However, human papilla cells lose their hair-inducing activity in later passage number. Ovine DP cells are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Ti 0.8 O 2 Nanosheets Have No Effect on Primary Dermal-Papilla Aggregation Properties. The data thus far has indicated that DP aggregation patterns reflect the ability to form hair (Sari et al, 2016). Having shown the promising effect of Ti 0.8 O 2 nanosheets in selective suppression of the CSC in lung cancer, we next evaluated whether treatment of normal cells with such a substance affected the viability of normal cells as well as their stem cell properties.…”
Section: Characterizationmentioning
confidence: 99%
“…Ti 0.8 O 2 Nanosheets Have No Effect on Primary Dermal-Papilla Aggregation Properties. The data thus far has indicated that DP aggregation patterns reflect the ability to form hair (Sari et al, 2016). Having shown the promising effect of Ti 0.8 O 2 nanosheets in selective suppression of the CSC in lung cancer, we next evaluated whether treatment of normal cells with such a substance affected the viability of normal cells as well as their stem cell properties.…”
Section: Characterizationmentioning
confidence: 99%
“…The stable detection of versican in the epidermis, specifically in the stratum germinativum as described by Zimmermann et al , could be observed in all tested skin samples. The study in ovine cell aggregates harvested from secondary wool hair follicles reported versican loss in adherent cells . Unlike in ovine, our equine adherent cells clearly expressed versican.…”
Section: Discussionmentioning
confidence: 43%
“…DPCs play a key role in generating hair bulbs and regulating hair-growth [5,47]. They are known to aggregate reactions that induce HF formation, and determine the hair bulb and shaft due to stem cell-like plasticity [48,49,50,51,52]. Therefore, the proliferation and stemness of DPCs can increase hair-growth.…”
Section: Discussionmentioning
confidence: 99%